2022
DOI: 10.1101/2022.11.07.22282040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of a Filtered Far-UVC Handheld Disinfection Device on Reducing Microbial Bioburden of Hospital Surfaces

Abstract: Objectives The Filtered Far UVC handheld disinfection device is a small portable device that emits far UVC at 222nm. The objective of this study was to evaluate the devices ability to kill microbial bioburden on hospital surfaces and compare it to manual cleaning using germicidal sodium hypochlorite wipes. Methods A total of 344 surfaces (86 observations per group) were sampled with 2 pairs of samples per surface a pre and a post sodium hypochlorite sample, and a pre and a post FFUV sample. The results were an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 2 In a recent separate study, we have reported the presence of MRSA on WOWs. 17 Another limitation is that any species identification for the aerobic bacterial colonies (ABCs) to determine recovery of commensals, multi-drug resistant organisms (MDROs) or other HAI-causing pathogens on PME was not performed for this study. Earlier cluster (c)-RCTs (5 out of 14) conducted on reducing MDROs and or HAIs, in a hospital environment indicated that either interventions such as use of cleaning and disinfecting agents (UV, copper, and bleach) or educational programs may be effective.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In a recent separate study, we have reported the presence of MRSA on WOWs. 17 Another limitation is that any species identification for the aerobic bacterial colonies (ABCs) to determine recovery of commensals, multi-drug resistant organisms (MDROs) or other HAI-causing pathogens on PME was not performed for this study. Earlier cluster (c)-RCTs (5 out of 14) conducted on reducing MDROs and or HAIs, in a hospital environment indicated that either interventions such as use of cleaning and disinfecting agents (UV, copper, and bleach) or educational programs may be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Under the new ACGIH guidelines, far-UVC represents a highly promising technology with the potential to significantly reduce indoor transmission of airborne 19 and even surface-borne pathogens. 20 Unlike complementary solutions such as air filtration and upper-room GUV, which clean the air only after it circulates and may fail to prevent the spread of infectious particles between individuals in close contact, far-UVC systems continuously disinfect the air throughout the room even while occupied. This suggests far-UVC may be able to rapidly neutralize pathogen-laden aerosols within the immediate breathing zones of occupants.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation was done to inform prototype development prior to any commercial use. Results of the surface disinfection efficacy are beyond the scope of this qualitative inquiry and are reported elsewhere (Navarathna et al, 2022).…”
mentioning
confidence: 99%